Technology and privacy : the new landscape - Agre, Philip; Rotenberg, Marc. (Cambridge, Mass. : MIT Press, 1997)
Annotation Privacy is the capacity to negotiate social relationships by controlling access to personal information. As laws, policies, and technological design increasingly structure people's relationships with social institutions, individual privacy faces new threats and new opportunities. Over the last several years, the realm of technology and privacy has been transformed, creating a landscape that is both dangerous and encouraging. Significant changes include large increases in communications bandwidths; the widespread adoption of computer networking and public-key cryptography; mathematical innovations that promise a vast family of protocols for protecting identity in complex transactions; new digital media that support a wide range of social relationships; a new generation of technologically sophisticated privacy activists; a massive body of practical experience in the development and application of data-protection laws; and the rapid globalization of manufacturing, culture, and policy making. The essays in this book provide a new conceptual framework for the analysis and debate of privacy policy and for the design and development of information systems. The authors are international experts in the technical, economic, and political aspects of privacy; the book's strength is its synthesis of the three. The book provides equally strong analyses of privacy issues in the United States, Canada, and Europe. Contributors:Philip E. Agre, Victoria Bellotti, Colin J. Bennett, Herbert Burkert, Simon G. Davies, David H. Flaherty, Robert Gellman, Viktor Mayer-Schonberger, David J. Phillips, Rohan Samarajiva.
Beyond the mirror world: privacy and the representational practices of computing / Philip E. Agre -- Design for privacy in multimedia computing and communication environments / Victoria Bellotti -- Convergence revisited: toward a global policy for the protection of personal data? / Colin J. Bennett -- Privacy-enhancing technologies: typology, critique, vision / Herbert Burkert -- Re-engineering the right to privacy: how privacy has been transformed from a right to a commodity / Simon G. Davies -- Controlling surveillance: can privacy protection be made effective? / David H. Flaherty --Does privacy law work? / Robert Gellman -- Generational development of data protection in Europe / Viktor Mayer-Schönberger -- Cryptography, secrets, and the structuring of trust / David J. Phillips -- Interactivity as though privacy mattered / Rohan Samarajiva.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Computer security; Data protection; Privacy, Right of; Computer Security; Sécurité informatique; Protection de l'information (Informatique); POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Computer security; Data protection; Privacy, Right of; INFORMATION SCIENCE/Technology & Policy; COGNITIVE SCIENCES/Psychology/Cognitive Psychology